A novel stylized model for platform ecosystem dynamics: Understanding IT service transformation from firm theory perspective. Issue 3 (2nd October 2018) - Kim, Dohoon
Abstract: This paper studies platform ecosystems, which refer to a novel solution built upon a platform coordinating business interactions between suppliers and users, particularly in the IT service sectors. Borrowing words from two fundamental firm theories—resource-based view (RBV) and transaction cost view (TCV)—we argue that the platform ecosystem works at the boundary between "market and hierarchy." We also develop a stylized model for the platform ecosystem, in which attributes like installed-base and heterogeneity and platform's investment are the primary ingredients for RBV and TCV, respectively. Our findings based on equilibrium analyses and simulations largely confirm that both RVB and TCV are valid for understanding a platform ecosystem. We, however, also identify some contingencies where RBV is limited, and propose a hypothesis that the platform' investment is more crucial for fostering an ecosystem. This implies that the platform starts from the point near market and maneuvers the ecosystem toward a hierarchy, utilizing its investment as a driver.